2009
DOI: 10.1002/hep.22860
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of c-Jun NH2-terminal kinase switches Smad3 signaling from oncogenesis to tumor- suppression in rat hepatocellular carcinoma

Abstract: Transforming growth factor beta (TGF-␤) signaling involves both tumor-suppression and oncogenesis. TGF-␤ activates the TGF-␤ type I receptor (T␤RI) and c-Jun N-terminal kinase (JNK), which differentially phosphorylate the mediator Smad3 to become COOHterminally phosphorylated Smad3 (pSmad3C) and linker-phosphorylated Smad3 (pSmad3L). T␤RI-dependent pSmad3C transmits a tumor-suppressive TGF-␤ signal, while JNK-dependent pSmad3L promotes carcinogenesis in human chronic liver disorders. The aim of this study is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 53 publications
(54 reference statements)
2
87
0
Order By: Relevance
“…[28][29][30] It was also shown that inhibition of C-terminal phosphorylation of Smad3 by JNK shifts Smad3-mediated signaling from oncogenesis to tumor suppression in rat hepatocellular carcinoma. 31 These findings suggest that multiple genes and signaling factors might be involved in the oncogenic conversion of TGF-β1 function in different tumor types.…”
Section: Ink4bmentioning
confidence: 94%
“…[28][29][30] It was also shown that inhibition of C-terminal phosphorylation of Smad3 by JNK shifts Smad3-mediated signaling from oncogenesis to tumor suppression in rat hepatocellular carcinoma. 31 These findings suggest that multiple genes and signaling factors might be involved in the oncogenic conversion of TGF-β1 function in different tumor types.…”
Section: Ink4bmentioning
confidence: 94%
“…Importantly, JNK1 is phosphorylated in human HCC samples (56). Direct evidence for the idea that JNK could be a promising drug target was provided by the findings that administration of the JNK inhibitor SP600125 to Cyld-deficient mice or DEN-treated rats blocked the development of HCC (46,57). SP600125 has also been shown to sensitize tumor cells, but not normal hepatocytes, to TRAIL, a major mediator of acquired immune tumor surveillance (58).…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…In actively growing hepatocytes, intracellular phosphorylation at Smad3L is increased (Fig. 2a, upper middle panel) [50][51][52]. Translocated to the nucleus, TNF-a-induced pSmad3L stimulates c-Myc transcription [53], which increases proliferation of hepatocytes and opposes the cytostatic action of the pSmad3C pathway [7].…”
Section: Introductionmentioning
confidence: 99%